Using Acanthamoeba spp. as a cell model to evaluate Leishmania infections. - Helena Lúcia Carneiro Santos; Gabriela Linhares Pereira; Rhagner Bonono do Reis; Igor Cardoso Rodrigues; Claudia Masini d'Avila; Vitor Ennes Vidal (PLoS Neglected Tropical Diseases)
Leishmaniasis represents a severe global health problem. In the last decades, there have been significant challenges in controlling this disease due to the unavailability of licensed vaccines, the high toxicity of the available drugs, and an unrestrained surge of drug-resistant parasites, and human immunodeficiency virus (HIV)-Leishmania co-infections. Leishmania spp. preferentially invade macrophage lineage cells of vertebrates for replication after subverting cellular functions of humans and other mammals. These early events in host-parasite interactions are likely to influence the future course of the disease. Thus, there is a continuing need to discover a simple cellular model that reproduces the in vivo pathogenesis. Acanthamoeba spp. are non-mammalian phagocytic amoeba with remarkable similarity to the cellular and functional aspects of macrophages. We aimed to assess whether the similarity reported between macrophages and Acanthamoeba spp. is sufficient to reproduce the infectivity of Leishmania spp. Herein, we analyzed co-cultures of Acanthamoeba castellanii or Acanthamoeba polyphaga with Leishmania infantum, Leishmania amazonensis, Leishmania major, and Leishmania braziliensis. Light and fluorescence microscopy revealed that the flagellated promastigotes attach to the A. castellanii and/or A. polyphaga in a bipolar and or random manner, which initiates their uptake via pseudopods. Once inside the cells, the promastigotes undergo significant changes, which result in the obligatory amastigote-like intracellular form. There was a productive infection with a continuous increase in intracellular parasites. However, we frequently observed intracellular amastigotes in vacuoles, phagolysosomes, and the cytosol of Acanthamoeba spp. Our findings corroborate that Leishmania spp. infects Acanthamoeba spp. and replicates in them but does not cause their rapid degeneration or lysis. Overall, the evidence presented here confirms that Acanthamoeba spp. have all prerequisites and can help elucidate how Leishmania spp. infect mammalian cells. Future work exposing the mechanisms of these interactions should yield novel insights into how these pathogens exploit amoebae.